2001
DOI: 10.22191/neha/vol31/iss1/12
|View full text |Cite
|
Sign up to set email alerts
|

A System for Ranking the Research Potential of 19th- and 20th- Century Farmstead Sites

Abstract: There is a need to establish a systematic and objective process for evaluating the research potential of farmstead sites so that intelligent choices can be made in deciding which sites should be investigated and managed and which should not. We propose the use of a checklist of traits that measures a site's research potential. Each of the traits in the checklist is assigned a score based on its value in providing important data for analyzing a site. The proposed checklist is a tool for organizing our observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…George and Meta were noted for their spirited discussions concerning pottery in its many forms. George and Terry collaborated on the important article: "A System for Ranking the Research Potential of Nineteenthand Twentieth-Century Farmstead Archaeology in the Northeast" (Miller and Klein 2002). In this article, Miller and Klein proposed ways of evaluating the research potential of a ubiquitous type of site frequently found but seldom studied.…”
Section: George In Delawarementioning
confidence: 99%
“…George and Meta were noted for their spirited discussions concerning pottery in its many forms. George and Terry collaborated on the important article: "A System for Ranking the Research Potential of Nineteenthand Twentieth-Century Farmstead Archaeology in the Northeast" (Miller and Klein 2002). In this article, Miller and Klein proposed ways of evaluating the research potential of a ubiquitous type of site frequently found but seldom studied.…”
Section: George In Delawarementioning
confidence: 99%